In-silico Studies of Usnic Acid against DENV-3 Methyltransferase - Roney, Miah; Dubey, Amit; Huq, A.K.M. Moyeenul; Mohd Fadhlizil Fasihi, Mohd Aluwi (Penerbit Universiti Malaysia Pahang, 2023)
There is currently no antiviral medication for dengue, a highly fatal tropical infectious disease spread by the Aedes aegypti and Aedes albopictus mosquitoes. The most conserved of the four Dengue serotypes and an essential element in viral replication, Dengue NS5 MTase is a promising therapeutic target. Applying in-silico techniques such as molecular docking, pharmacokinetics, and pharmacophore analysis, we intend to discover novel inhibitors against Dengue NS5 MTase from Usnic acid. In the end, the docking results indicated that usnic acid had satisfactory docking values of -9.3 kcal/mol. We were able to confirm that the usnic acid had higher potential scores in docking and bound amino acids than the reference compound during our in-silico evaluation. Molecular docking, pharmacokinetics, and pharmacophore evaluations revealed that usnic acid has high pharmacological potential. Additionally, we anticipate that the testing in vitro and in vivo of usnic acid would indicate potential medicinal benefits.